Various Inc-type plasmids and lineages of Escherichia coli and Klebsiella pneumoniae spreading blaCTX-M-15, blaCTX-M-1 and mcr-1 genes in camels in Tunisia. (December 2019) - Saidani, Mariem; Messadi, Lilia; Mefteh, Jomâa; Chaouechi, Amira; Soudani, Alya; Selmi, Rachid; Dâaloul-Jedidi, Monia; Ben Chehida, Faten; Mamlouk, Aymen; Jemli, Mohamed Habib; Madec, Jean-Yves; Haenni, Marisa
Highlights: E. coli and K. pneumoniae isolates were highly susceptible, except to tétracyclines. The proportion of ESBL phenotype was low (1.3% in E. coli, 0.4% in K. pneumoniae ). Camels are reservoirs of fluoroquinolone resistance, mcr-1 and bla ESBL genes. Various Inc-types plasmids were found, such as IncHI2 carrying bla CTX-M-1 and mcr-1 . Abstract: Objectives: Resistance to extended-spectrum cephalosporins, fluoroquinolones and colistin is under constant scrutiny in food-producing animals worldwide. However, little is known about camels, which provide milk and meat for human consumption, and are attractions for tourists to ride in arid regions. This study assessed the role of camels as potential reservoirs of these resistance determinants. Methods: Faecal swabs were collected from 232 camels in Tunisia between April 2016 and July 2018. Enterobacteriaceae were detected on MacConkey agar and extended-spectrum β-lactamase (ESBL)-producers on the same medium supplemented with cefotaxime. Antimicrobial resistance was assessed by disc diffusion, and ESBL-producing isolates were further characterised by phylogrouping (for Escherichia coli, E. coli ) and multilocus sequence typing. Genetic support of the bla ESBL and mcr-1 genes was identified by plasmid-typing and Southern blot. Results: E. coli were identified in 163 of 232 (70.3%) and Klebsiella pneumoniae ( K. pneumoniae ) in 16 of 232 (6.9%) of the dominant flora. Three E. coli and one K. pneumoniae (1.3% and 0.4%, respectively) were found on cefotaxime-enriched media. One K. pneumoniae and one E. coli from a tourist farm harboured the bla CTX-M-15 gene on an IncY plasmid, while the two E. coli from the butchery sector displayed the bla CTX-M-15 gene on an IncI1 plasmid and colocalisation of the bla CTX-M-1 and mcr-1 genes on an IncHI2 plasmid. Conclusions: This study reported ESBL-producing Enterobacteriaceae in Tunisian camels from both tourist and meat-producing sectors. This was the first description of the mcr-1 gene in a meat-producing camel. Although not alarming, this context needs specific attention to avoid camels becoming a bigger reservoir for multidrug-resistant Enterobacteriaceae.